Influence of sex and phenotype on cardiac outcomes in patients with Fabry disease. Issue 23 (10th February 2021) - El Sayed, Mohamed; Hirsch, Alexander; Boekholdt, Matthijs; van Dussen, Laura; Datema, Mareen; Hollak, Carla; Langeveld, Mirjam
Abstract : Objective: This study describes the influence of sex and disease phenotype on the occurrence of cardiac events in Fabry disease (FD). Methods: Cardiac events from birth to last visit (median age 50 years) were recorded for 213 patients with FD. Patients were categorised as follows : men with classical FD (n=57), men with non-classical FD (n=26), women with classical FD (n=98) and women with non-classical FD (n=32), based on the presence of classical FD symptoms, family history (men and women), biomarkers and residual enzyme activity (men). Event rates per 1000 patient-years after the age of 15 years and median event-free survival (EVS) age were presented. Influence of disease phenotype, sex and their interaction was studied using Firth's penalised Cox regression. Results: The event rates of major cardiovascular events (combined endpoint cardiovascular death (CVD), heart failure (HF) hospitalisation, sustained ventricular arrhythmias (SVAs) and myocardial infarction) were 11.0 (95% CI 6.6 to 17.3) in men with classical FD (EVS 55 years), 4.4 (95% CI 2.5 to 7.1) in women with classical FD (EVS 70 years) and 5.9 (95% CI 2.6 to 11.6) in men with non-classical FD (EVS 70 years). None of these events occurred in women with non-classical FD. Sex and phenotype significantly influenced the risk of major adverse cardiovascular event. CVD was the leading cause of death (75%) to which HF contributed most (42%). The overall rate of SVA was low (14 events in nine patients (4%)). Conclusions: Sex and phenotype greatly influence the risk and age of onset of cardiac events in FD. This indicates the need for patient group-specific follow-up and treatment.